2021
DOI: 10.1111/tbed.14402
|View full text |Cite
|
Sign up to set email alerts
|

Tembusu virus infection in laying chickens: Evidence for a distinct genetic cluster with significant antigenic variation

Abstract: Tembusu virus (TMUV) associated disease is a growing cause of egg production decrease and encephalitis in domestic waterfowl, with expanding distribution. In previous studies, TMUV isolates were phylogenetically classified into two genetic lineages and different clusters with varied pathogenicity. However, little is known about the phenotypic and virulence characteristics of cluster 3 isolates within the duck TMUV lineage. In this study, the etiological agent causing egg drop in a laying chicken farm in southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 42 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…This large-scale transportation of poultry and intensive farming has contributed to the transmission rate of TMUV, allowing it to quickly spread across the country. However, we cannot ignore the possibility that TMUV can be transmitted by birds, such as pigeons; there is already evidence that it can be transmitted in waterfowl and other birds [16,17], which will create huge challenges in its prevention and control. We also need to be aware that this mode of transmission is similar to that of influenza viruses and may pose potential public health risks [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This large-scale transportation of poultry and intensive farming has contributed to the transmission rate of TMUV, allowing it to quickly spread across the country. However, we cannot ignore the possibility that TMUV can be transmitted by birds, such as pigeons; there is already evidence that it can be transmitted in waterfowl and other birds [16,17], which will create huge challenges in its prevention and control. We also need to be aware that this mode of transmission is similar to that of influenza viruses and may pose potential public health risks [53].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that TMUV can infect not only ducks but other avian species, including chickens, geese, pigeons, and sparrows, suggesting that TMUV has a wide host range. Some studies have found that TMUV does not exhibit a bird species barrier and that mosquitoes can play an important role in the transmission of TMUV [9,[15][16][17]. The injection of TMUV into the brains of mice has shown that the mice develop significant neurological symptoms and die [18].…”
Section: Introductionmentioning
confidence: 99%
“…Of the several important viruses that may become vertebrate pathogens, both TMUV and GETV were found initially in Malaysia and have been recently found in many places in China (Hamel et al, 2021;Li et al, 2022). TMUV can cause encephalitis and neurological disorders in birds and induce severe egg drop syndrome in ducks (Yu et al, 2022). TMUV was reported to cause epidemics affecting ducks in China in 2010, leading to huge economic losses and attracting widespread attention (Cao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A VN test to measure the cross-reactivity of these representative isolates was carried out using the microneutralization method performed on LMH cells as described previously [21] with some modifcations. Briefy, GoAstV isolates were individually adapted in LMH cells by fve serial passages.…”
Section: Cross-reactivity Assay Of Astv Isolatesmentioning
confidence: 99%